2016
DOI: 10.1016/j.hrthm.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial comparing pulmonary vein isolation using the SmartTouch catheter with or without real-time contact force data

Abstract: This randomized multicenter study demonstrated that CF data availability was associated with reduced acute PV reconnection but not improved 1-year success rates, procedural and fluoroscopy times, or complication rates. There was a reduction in extremes of CF, above and below the study target range, suggesting greater CF control during ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(117 citation statements)
references
References 31 publications
6
108
2
1
Order By: Relevance
“…6 A recent randomized, multicenter study, however, showed that CF data availability was associated with reduced acute PV reconnections but not improved 1-year success rates, procedure and fluoroscopy times, or complication rates. 7 The failure of CF monitoring to improve clinical outcome of AF ablation might be due to a lack of information on the catheter stability as well as the precise location of ablated lesions, and subsequent heterogeneous ablation intensity. A new ablation annotation system (CARTO3 System, PVI: Guided Novel Annotation 0.67 mL/min/kg for 15 s, followed by a saline bolus flush.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A recent randomized, multicenter study, however, showed that CF data availability was associated with reduced acute PV reconnections but not improved 1-year success rates, procedure and fluoroscopy times, or complication rates. 7 The failure of CF monitoring to improve clinical outcome of AF ablation might be due to a lack of information on the catheter stability as well as the precise location of ablated lesions, and subsequent heterogeneous ablation intensity. A new ablation annotation system (CARTO3 System, PVI: Guided Novel Annotation 0.67 mL/min/kg for 15 s, followed by a saline bolus flush.…”
Section: Subjectsmentioning
confidence: 99%
“…7 The failure of CF monitoring to improve clinical outcomes of AF ablation might be due to a lack of information on catheter stability during energy delivery, and heterogeneous RF ablation intensity. If so, real-time information on catheter stability and ablation intensity would possibly improve lesion completeness.…”
Section: Efficacy Of Visitag Modulementioning
confidence: 99%
“…This confirms that CF is only one of multiple factors that determine lesion efficacy and safety. 15 Three other small prospective randomised studies have compared CF versus non-CF-sensing catheter ablation. These studies have shown that some operators are able to estimate CF with a high degree of accuracy when CF information is not available and may explain why, when the CF information was available, none of these studies demonstrated a statistically significant improvement in long-term outcomes.…”
Section: Clinical Impact Of Contact Force Technologiesmentioning
confidence: 99%
“…Additionally, a recent randomized head-to-head comparison study that sought to see if contact force improved results demonstrated that, despite contact force data being associated with reduced acute PV reconnection, it did not improve oneyear success rates. 30 Though contact force information is helpful, many operators prefer other options because contact force catheters are often stiff and unwieldy. If an operator does choose to use a contact force catheter, then expert guidelines recommend a starting point minimum targeted contact force of 5 g to 10 g (Class IIa, LOE C).…”
Section: Ablation Lesion Formationmentioning
confidence: 99%